Teacher’s Competencies: A Modern Discourse and the Rhetoric - Mehmet ŞİŞMAN (İnönü Üniversitesi Eğitim Fakültesi Dergisi)
Teacher training is an issue or a problem since the field is not isolated from the general problems of higher education. After the duty of teacher training was assigned to universities in the early 1980s, some persistent problems were also transferred to the higher education remaining to be resolved. Moreover, new problems also emerged. Faculties of education in Turkey recently have become one of the most preferred faculties, which is good news because this development implied an improvement in the status of the teaching profession. But as of 2009-2010 academic year, like in the 70s, Higher Education Institution readopted the former practice which allowed Science & Arts faculties to train teachers in undergraduate programs. Thus, there emerges the risk of reversal from positive developments achieved in favor of the teaching profession so far. In many countries, a change in paradigm is on the agenda in terms of the teacher training programs and practices, the learning and teaching processes, and the roles of teachers. Recent approaches based on interpretive paradigm and critical theory have introduced new perspectives related to education, school, and teaching. In the next decades, some issues have to be redefined such as restructuring the school and the learning process, student and teacher roles, and school leadership and teaching. In this article, teacher education in developed countries has been reviewed in the context of “teacher standards" which have been a current issue before the policy makers and other stakeholders. Moreover, recent discussions and problems were reviewed in the light of teacher competencies and standards.